Some remarks on the state od advance of the European legal systems providing euthanasia and/or the assisted suicide (TEST BioLaw Journal - Rivista di BioDiritto, 2022)
Fundamental rights have a universal extent: therefore, the work aims at drawing a comparative-law picture regarding the legal systems providing, in the field of the “end of life”, euthanasia and/or assisted suicide (Italy, Switzerland, Austria, at the first level; Belgium, Netherlands and Luxembourg at the second degree; Germany and Spain at the last stage). Attempt is made to promote the most valuable (according to the writer’s opinion) elements and to highlight their flaws, in order to outline, by some necessary adjustment, an “end of life” legislation worthy of a non authoritative country.
Keywords: Assisted suicide; euthanasia; disposability; criminal liability; self-determination